Equating the right-hand sides of the two equations gives you a quadratic equation. If you have trouble solving it, please post your solution steps so that we can give you feedback.
In plain text, it is customary to write x^2 for .
I'm to solve simultaneous equation :
y = −3x + 2
y = 2x2 −7x−4
I know the what the answer should be but i never seem to get it, so im clearly doing it wrong!
Any help especially on how to solve it would really be appreciated!
Equating the right-hand sides of the two equations gives you a quadratic equation. If you have trouble solving it, please post your solution steps so that we can give you feedback.
In plain text, it is customary to write x^2 for .
Thank's
Heres one of my attempts...theres been a few!
0 = 2x^2 - 4x - 6
( 2x+3)(x-2)
2x+3 + 0 and x-2 = 0
x is -1.5 and x is 2
Im supposedly to have the answer of -1 and 5 somehow, but no idea how !
Thanks for any input in advance
(2x+3)(x-2) = 2x^2 - x - 6 ≠ 2x^2 - 4x - 6.
If you know the quadratic formula, you should use it.
The solutions are x = -1 and x = 3. The value x = 5 does not fit the original equations.